Introducing an ecosystem services approach to quarry restoration - King, Helen P. (Cranfield University, 2013)
The ecosystem services approach is an emerging trend in policy, academia and land management, as seen by its inclusion in the National Planning Policy Framework, Natural Environmental White Paper, and the UK Sustainability Development Strategy. Minerals quarrying can impact significantly on natural and social environments, and subsequently extraction is highly regulated. The Mineral Products Association (‘MPA'; a trade organisation for the minerals industry) recognises that the industry would benefit from a better understanding of its relationship with ecosystem services. The MPA works with the RSPB and Natural England on the ‘Nature After Minerals' programme, to help minerals companies take a biodiversity-led approach to quarry restoration. Increasing the effectiveness of this programme, and awareness amongst landowners, policymakers, and the general public is seen as key to increasing high-quality land restoration which benefits local communities and wildlife. This report shows how an ecosystem services approach could offer a systematic framework to enhance, structure, and communicate the benefits which restored land provides to society. It provides information to enable the minerals products industry to evaluate and begin to develop an ecosystem services approach to quarry restoration. Subsequently the report i) outlines the ecosystem services approach, ii) identifies its relevance to the minerals industry, iii) identifies how an ecosystem services approach may be applied to quarry restoration, and iv) provides recommendations for the minerals industry which support the introduction of an ecosystem services into quarry restoration. Findings include the types of ecosystem services that restored quarries can (potentially) generate and associated public benefits specifically for four common habitat types: heathlands, grasslands, wetlands and farmland. The report gives examples of how ecosystem services from these habitats may be valued. A number of business opportunities and threats are considered in relation to ecosystem service trends. A key issue for the minerals industry to address is the lack of formal reporting and centralised recording of habitats created through restoration. Recommendations for the mineral industry to consider include: 1. Developing a ‘habitat creation' database to enable transfer studies of the value of ecosystem services 2. Developing an ecosystem services classification and appraisal guide to allow rapid assessment of such services in minerals contexts 3. Integrating ecosystem services into planning applications in order to identify local priorities, enhance stakeholder engagement, and where appropriate pave the way for Payments for Ecosystem Services (PES) schemes 4. Undertaking a full assessment of potential market opportunities and risks Developing links to other programmes and databases using an ecosystem service approach such as RESTORE, the UK NEA, BESS, TESSA, AIRES, and InVEST
Natural Environment Research Council Internship Scheme : Natural Capital & Ecosystem Services, Final Report 12th July 2013.